CHARACTERISTICS OF EDUCATIONAL STANDARD DEVELOPMENT IN INFORMATICS (TRAINING DIRECTION 0403020) ﻿ - Akimenko, B.B.; Nikitchenko, M.C. (Journal of Information Technologies in Education (ITE), 2010)
In the paper main principles of development and structure of educational standard in the direction 040302 INFORMATICS are described.